Odpowiedzi

Najlepsza Odpowiedź!
2009-10-31T12:12:50+01:00
6-2/3x >4-4/3 x
-2/3x +4/3 x > -6 +4
2/3x > -6 / x3
2x > -18 / x :2
x > - 9
zad2/79
rozwiąż nierówności;

c)2/3 x-2/9 x>x-2/2
4/9x - x > - 1
- 5/9x > -1 / x (-1)
5/9x< 1 / : 5/9
x< 9/5
x< 1i 4/5

e)(x-2)(x+3)≥(x-5)(x-6)
x² +3x - 2x - 6 ≥ x² - 6x - 5x + 30
x+11x ≥ 36
12x≥ 36 / :12
x≥ 3


f)(x-2)²+6≥(x-2)(x-1)

x² -2x - 2x + 4 ≥ x² - x - 2x +2
- 4x + 3x ≥ -4 +2
-x ≥-1 / x (-1)
x≤1

g)(x+5)(x+4)>x²+7

x² +4x + 5x + 20 > x² +7
9x > - 13 / :9
x> - 13/9
1 4 1